Making Recording and Analysis of Chief Complaint a Priority for Global Emergency Care Research in Low‐income Countries. (27th November 2013) - Mowafi, Hani; Dworkis, Daniel; Bisanzo, Mark; Hansoti, Bhakti; Seidenberg, Phil; Obermeyer, Ziad; Hauswald, Mark; Reynolds, Teri A.; Cone, David C.
Abstract The chief complaint is a patient's self‐reported primary reason for presenting for medical care. The clinical utility and analytical importance of recording chief complaints have been widely accepted in highly developed emergency care systems, but this practice is far from universal in global emergency care, especially in limited‐resource areas. It is precisely in these settings, however, that the use of chief complaints may have particular benefit. Chief complaints may be used to quantify, analyze, and plan for emergency care and provide valuable information on acute care needs where there are crucial data gaps. Globally, much work has been done to establish local practices around chief complaint collection and use, but no standards have been established and little work has been done to identify minimum effective sets of chief complaints that may be used in limited‐resource settings. As part of the Academic Emergency Medicine consensus conference, "Global Health and Emergency Care: A Research Agenda, " the breakout group on data management identified the lack of research on emergency chief complaints globally—especially in low‐income countries where the highest proportion of the world's population resides—as a major gap in global emergency care research. This article reviews global research on emergency chief complaints in high‐income countries with developed emergency care systems and sets forth an agenda for future research on chief complaints in limited‐resource settings.